Ownership diversity and the risk-taking channel of monetary policy transmission - Caselli, Giorgio; Figueira, Catarina; Nellis, Joseph G. (Cambridge University Press, 2020)
This paper joins a rapidly growing body of literature that aims to uncover the link between monetary policy and bank risk taking. We investigate the hypothesis that the ownership composition of the banking system moderates monetary policy transmission via the risk-taking channel. Borrowing measures used in ecology to quantify diversity of species within an ecosystem and first applied to the field of finance by Michie, J. and Oughton, C. 2013. ‘Measuring Diversity in Financial Services Markets: A Diversity Index’, Centre for Financial and Management Studies Discussion Papers no. 113, this paper shows that the impact of exogenous monetary policy shocks on banks’ probability of default is reduced in countries with greater ownership diversity. We also find that—ceteris paribus—shareholder- and stakeholder-oriented banks located in more ownership-diverse systems tend to have a lower appetite for risk than their counterparts operating in less diverse markets. These results are robust across several econometric specifications and emphasise the stabilising role played by ownership diversity in modern financial systems. At the same time, our evidence suggests that a more interdisciplinary approach, firmly grounded in the applied, empirical research methodology, can provide novel and useful insights into the implications of monetary policy for financial and economic outcomes.